Peran Pendidikan Agama Islam dalam Membentuk Kesadaran Ekologis dan Sikap Peduli Lingkungan Siswa di SDN 158 Mundan - Irma Irma; Suherni Suherni; Jupri Jupri; Amaluddin Amaluddin (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping students' character and moral awareness, including ecological awareness and environmental stewardship. This study aims to analyze how PAI can foster ecological awareness and environmental stewardship among students at SDN 158 Mundan. The method used was descriptive qualitative with a case study approach. Data were obtained through lesson observations, interviews with PAI teachers, and student questionnaires. The results indicate that integrating Islamic values ​​into learning materials, such as the concept of caliphate, trust, and environmental stewardship, can increase students' awareness of the importance of environmental protection. Students demonstrate environmentally conscious behavior through simple actions such as keeping the classroom clean, planting plants, and conserving energy. Furthermore, teachers act as role models by implementing environmentally friendly behaviors in schools. These findings confirm that PAI not only teaches rituals and morals but can also shape students' ecological awareness through the instillation and instillation of Islamic values. This study recommends strengthening the PAI curriculum by integrating environmental values ​​and improving teacher training to more effectively implement environment-based learning.